Higher Mortality Associated With New-Onset Atrial Fibrillation in Cancer Patients: A Systematic Review and Meta-Analysis - Murtaza, Minha; Baig, Mirza Mehmood Ali; Ahmed, Jawad; Serbanoiu, Liviu Ionut; Busnatu, Stefan Sebastian (Frontiers in Cardiovascular Medicine, 2022)
Aims: This research was conducted to evaluate the mortality outcome of cancer patients with new-onset atrial fibrillation. We also aimed to assess if there was any confounding relation between mortality of these patients and surgical intervention. Materials and Methods: A systemic search was conducted from electronic databases (PubMed/Medline, Cochrane Library, and Google Scholar) from inception to 7th February 2022. All statistical analysis was conducted in Review Manager 5.4.1. Studies meeting inclusion criteria were selected. Only those studies were selected that involved cancer patients without pre-existing atrial fibrillation, and compared mortality rate between the patients who developed atrial fibrillation and those who did not. A random-effect model was used when heterogeneity was seen to pool the studies, and the result was reported in the odds ratio (OR) and corresponding 95% Confidence interval (CI). Results: Eighteen studies were selected for meta-analysis. Statistical analysis showed that those cancer patients who subsequently developed atrial fibrillation had a significantly higher mortality rate as compared to those who did not (OR= 1.90 [1.65, 2.19]; p <0.00001; I2= 100%). We also separately analyzed the mortality risk in surgery group and non-surgery group. Statistical analysis showed that there was significantly higher mortality rate associated with new-onset atrial fibrillation in cancer patients in the surgery group (OR= 3.68 [2.29, 5.94]; p < 0.00001; I2= 61%) as well as those in the non-surgery group (OR= 1.64 [1.39, 1.93]; p <0.00001; I2= 100%). Conclusion: Cancer patients who subsequently developed atrial fibrillation had higher mortality rate as compared to those cancer patients who did not develop atrial fibrillation. Higher mortality rate was seen in both surgical and non-surgical subgroups. This implies that extra care and specific measures must be taken in the management of cancer patients with new-onset atrial fibrillation.